Speeches and migratory practices: contradictions, hypocrisies and perverse effects of current policies - Mayeur, Carolina (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article is a contribution of the author, as an expert in the field, to the elaboration of a document commissioned by the European Commission on Migrations, within the framework of its activities, from a group of independent experts. The purpose of the document is to present some points for the member states of the Council of Europe to consider which will serve to orientate them in the adoption of future policies with respect to the management of migratory movements, based on a critical evaluation of the current situation. It also aims to be influential in the necessary definition of a common policy with respect to migration within the framework of the European Union. This document, the final draft of which has been commissioned from the English consultant, John Salt, will be discussed at the Commission meeting which is to take place in the spring of 1998. The contents of the article aim to expose the contradictions and hypocrisy which characterise European governments’ current policies. They stem from a crisis in the migratory model dominant in the 80s, the most visible characteristic of which is the presence in almost all European countries of illegal immigrants. It points out some of the contradictions of this model, both in its facet of controlling migratory movements and integration policies as well as in the alternative strategies which have been proposed, with arguments and data taken from studies with different methodological approaches. Two important ideas are underlined: 1.ª) restrictive immigration and political asylum policies are conducive to illegal immigration, and 2.ª the relationship established between greater control/better integration has not been demonstrated. Finally, it proposes Alain Touraine’s recent analyses on «demodernisation» as a possible theoretical integrative framework for the ideas presented.